2012
DOI: 10.1002/pip.2230
|View full text |Cite
|
Sign up to set email alerts
|

Dust-induced shading on photovoltaic modules

Abstract: The effect of dust on photovoltaic modules is investigated with respect to concentration and spectral transmittance. Samples were collected in the form of raw dust as well as accumulated dust on exposed sheets of glass at different tilt angles. Spectral transmittance of the samples was determined. Transmittance variation between top, middle and bottom was identified for samples collected at different inclinations, where the worst case was seen at a tilt angle of 30 o with a nonuniformity of 4.4% in comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
93
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 192 publications
(117 citation statements)
references
References 20 publications
6
93
0
1
Order By: Relevance
“…It can be postulated that the soiling at ROTA has an equal impact on the performance between the technology types. On the contrary, Qasem et al (2012) in Kuwait found that the transmittance is affected more by dust at lower wavelengths. Therefore, wider band gap PV technologies such as a-Si and CdTe are more affected by dust deposition than c-Si and CIGS.…”
Section: Transmittancementioning
confidence: 91%
See 4 more Smart Citations
“…It can be postulated that the soiling at ROTA has an equal impact on the performance between the technology types. On the contrary, Qasem et al (2012) in Kuwait found that the transmittance is affected more by dust at lower wavelengths. Therefore, wider band gap PV technologies such as a-Si and CdTe are more affected by dust deposition than c-Si and CIGS.…”
Section: Transmittancementioning
confidence: 91%
“…The artificial dust collected from ROTA was then deposited onto the surface of the storage container. The deposition of dust was performed by free fall technical using a cylindrical tube to minimize the influence of wind flow as performed by Qasem et al (2012). The accumulated dust on the container was coated with carbon; a recommended material as it doesn't interfere with the characteristic X-ray peaks from the elements in the sample and prevents static charging of the dust before the SEM and EDS experiments were applied.…”
Section: Investigation Of Dust Propertiesmentioning
confidence: 99%
See 3 more Smart Citations